Drug Therapy for Swine Flu - An Overview - D.SATHIS KUMAR,; DAVID BANJI,; K.RAJASHEKAR,; CH.RAHUL,; A.KRANTHI,; M.ADARSH VERMA,; P.AJAYKUMAR,; CH.KRISHNACHAITANYA, (International Journal of Pharma and Bio Sciences, 2010)
Swine flu also known as H1N1 has become the worlds fastest moving influenza pandemic, sweeping across 177 countries in the four months since it was first identified, according to the US centres for Disease control and prevention based in Atlanta. More than 1 million people have already contracted the virus in New york alone, according to estimates by the cities health department. It is a form of influenza that originated in pigs but can be caught by, and spread among people. This is a dangerous scenario in 21st century. So, there is a need to prevent and to treat the swine flu all over the world. Clinical trails are going on for treating this swine flu but still there is no proper drug therapy for this disease. Here we reveal that complete drug therapy for this disease for swine flu in several medicinal systems and prevention techniques like vaccine therapy.